Incidente de desconsideração da personalidade jurídica e a tutela provisória de urgência cautelar de arresto - Camilo, Eliana Figueiredo (2025)
This study seeks to explore the dialogical interface that exists between the institutes of disregarding legal personality and the effectiveness of the rights expressed by the legal provision for granting provisional and emergency relief. The research problem deals with issues related to the effectiveness of the jurisdiction involving the legal personality and the default of its obligations to its creditors. The question is whether provisional injunctive relief of seizure is possible in the incident of the disregard of legal personality. The aim is to analyze the effectiveness of rights that converge through instrumentalization by means of Civil Procedural Law. The deductive method will be used, and the research technique will be to consult the bibliographic collection of doctrine in general, such as literary works, theses, dissertations and scientific articles related to the theme proposed in this study and, equally, case law decisions in conjunction with the reasoning attributed to the deductive method and the golden bridge drawn by social reality combined with the essential studies of the legal system. The results of the research will be respectively: [i] how the incident of disregarding the legal personality and provisional guardianships, in particular, the precautionary provisional guardianship of seizure can be used as an instrument of effectiveness of the jurisdiction and; therefore; [ii] making effective the right of creditors and also the jurisdictional activity instrument of realization of rights, solution of conflicts, consolidating a state of legal security and social peace; and, furthermore. The research contributes to bring up the ever-recurring discussion of how the implementation and instrumentalization of institutes aimed at making rights effective deals with the need to focus on means that make the satisfaction of creditors' rights effective. Furthermore, questions about the effectiveness of rights always play an meaningful role in scientific contributions, thus corroborating the importance of the study in question